Two-dimensional simulations of vortex-induced vibration of a circular cylinder - Mutlu, Asim Ozan; Bayraktar, Meral; Bayraktar, Seyfettin (SAGE PUBLICATIONS LTD, 2021)
In the present study, one of the cross-disciplinary problems known as vortex-induced vibration is numerically investigated. Effects of four different low mass-damping ratios; zeta = 0.013, 0.028, 0.074, and 0.124 of a smooth cylinder are taken into account for transition of shear layer 2 (TrSL2) type flow that falls between the Reynolds numbers from 2500 to 10,830 utilizing a two-dimensional cylinder that is free to move in normal-direction. Unsteady Reynolds-Averaged Navier-Stokes solutions indicate that the general trend is well captured with the adopted shear stress transport k-omega turbulence model, however, due to two-dimensional limitations some results are not consistent with experimental data. An inverse relation between the mass-damping ratio and the transition from the upper to the lower branch is detected. Change of drag and lift coefficients with the reduced velocities revealed that the maximum drag coefficient increases with reduced velocity until it reaches Ur = 5 and then decreases dramatically while the lift coefficients decrease consistently from the beginning.
Keywords: Vortex induced vibration; unsteady Navier– Stokes equations; turbulence; cylinder; one-degree-of-freedom; FLOW-INDUCED VIBRATIONS; VERY-LOW MASS; NUMERICAL-SIMULATION; FREQUENCY-RESPONSE; AMPLITUDE; DYNAMICS; FREEDOM; FORCES; WAKES; Engineering